ON THE BOUNDARY OF TETHYAN TECTONIC DOMAIN ON NORTHEASTERN MARGIN OF THE TIBETAN PLATEAU - Hou Q.Y.; Zhao Z.D.; Chen Y.L.; Zhang B.R.; Zhang H.F.; Zhang L. (My University, 2006)
It is very important to discovery the northern boundary of eastern Tethyan tectonic domain not only for constraining its range and evolution, but also for establishing the tectonic affinity of microcontinents or terranes in China. Early Paleozoic ophiolitic suites preserved in Qilian orogenic belt give very great opportunities to emphasize insights into this scientific problem. This paper provides geochemical constraints on it. Systematic elements Sr-Nd-Pb isotopic compositions for pillow basalts from these ophiolitic complexes are presented in this article. It is shown that the Nd and Pb isotopic compositions of mantle sources for them are similar to those of mantle sources for the MORB-type basalts in the Palaeo-, Ceno-Tethys and Indian Ocean. (Δ207 Pb/204 Pb), of these basalts ranges from 9.1 to 24.3 (Average: 14.7); (Δ208/ 204Pb), is between 9.1 and 101.1 (Average: 55.3). The age-corrected Nd and Pb isotopic characteristics indicate that these ophiolitic units were derived from the mantle source that had the Indian MORB-type isotopic signature. Therefore, we have suggested that ancient oceanic mantle for these Early Paleozoic ophiolitic complexes was an important branch of Proto-Tethys. It could be summarized that the ancient oceans developed in eastern Tethyan tectonic domains become progressively younger from north to south in China. Further, the evolution of Central cordillera is the epitome of tremendous geodynamics setting that some continental slivers were rifted from the northern margin of Gondwanaland and amalgamation (or accretion) of these to form proto-East and SE Asia.
Keywords: EASTERN TETHYAN TECTONIC DOMAIN; OPHIOLITES; QILIAN OROGENIC BELT; TIBETAN PLATEAU